World Experience in the Digitalization of Public Administration in the Development of the Tourist and Recreational Sphere - Boretska, N.; Krapivina, G. (Економічний вісник Донбасу, 2021)
The article summarizes the world experience in the digitalization of public administration in the development of the tourist-reactionary sphere and demonstrates the feasibility of introducing digitalization in the adaptation of public administration to the realities of the modern world. It is shown that in the world practice, the digitalization of state management of the development of the tourist and recreational sphere is based on a statistical description of tourist and recreational problems; creation of models for predicting the consequences of government decisions on the development of the tourism and recreation sector; means of measuring the economic efficiency of the development of various forms of organizing the use of the free time of the population. In particular, the digitalization of state management of the development of the tourist and recreational sphere in Israel, Turkey and Puerto Rico demonstrates the feasibility of the goal of digitalization for the state solution of the problems of managing the intensity of visitor flows from the centers of population concentration in the destination and predicting the economic effect of this. In Israel, the digitalization of state management of the development of the tourist and recreational sphere is aimed at increasing the volume of foreign currency entering the country through tourism, and its share in budget revenues, as well as maximizing the saving of resources for the development of local tourism. The digitalization of the Turkish Ministry of Tourism allows government decisions to be made to assess the likely and optimal economic effect from the development of destinations and their qualitative structure within the regional economy; balance the maximum supply and demand of tourism and recreation projects; calculate the surplus and deficit of tourist and recreational services; to maximize the level of costs necessary for the optimal economic effect on the development of the tourist and recreational sphere; optimize the distribution of funds by destination, depending on the potential for the development of the tourist and recreational sphere in each of them; to optimize the seasonal distribution of factors of activity of the tourist and recreational sphere; Determine the latent or existing cost limit associated with changing key assumptions, inputs, and optimal outcomes for the development of destinations. The practice of digitalization of state management of the development of the tourist and recreational sphere in Bulgaria (Golden Sands, Sunny Beach, Albena, etc.) shows that the introduction of the principle of integrated and centralized digitalization of state management of their development deserves a positive assessment. The digitalization of state management of the development of the tourist and recreational sector in the Pacific Ocean region makes it possible to determine the destinations of visitors that attract visitors in different seasons, which determines the characteristics of the destinations; logistic connections and characteristics of transport and information means for realizing the possibilities of communication between the point of departure and the point of destination in a certain period of time. In the countries of the South Adriatic, the digitalization of state management of the development of the tourist and recreational sphere makes it possible to justify the estimated and project estimates for the renewal of destinations. The digitalization of public administration in the development of French destinations gives rise to government decisions on the implementation of design programs for the use of territories favorable for tourism and recreation and to regulate the main parameters of their development. In the United States, the digitalization of the National Park Service is making it possible to implement projects to create nature reserves and tourist and recreational centers in historic cities. У статті узагальнено світовий досвід діджиталізації державного управління розвитком туристично-рекреаційної сфери та демонструється доцільність запровадження діджиталізації в пристосуванні державного управління до реалій сучасного світу. Показано, що у світовій практиці діджиталізація державного управління розвитком туристично-рекреаційної сфери ґрунтується на статистичному описі туристично-рекреаційних проблем; створенні моделей прогнозування наслідків державних рішень з розвитку туристично-рекреаційної сфери; засобах виміру економічної ефективності від розвитку різноманітних форм організації використання вільного часу населення. Зокрема, діджиталізація державного управління розвитком туристично-рекреаційної сфери Ізраїлю, Туреччини та Пуерто-Ріко демонструє доцільність мети діджиталізації проблем управління інтенсивністю потоків відвідувачів з центру зосередження населення до дестинацій та прогнозування економічного ефекту від цього, що особливо цікаво та докладно обґрунтовано. В Ізраїлі діджиталізація державного управління розвитком туристично-рекреаційної сфери має за мету збільшення обсягів іноземної валюти, яка надходить у країну завдяки туризму, та її частки в доходах бюджету, а також максимальну економію ресурсів на розвиток місцевого туризму. Діджиталізація міністерства туризму Туреччини дозволяє одержати для прийняття рішень оцінки ймовірного й оптимального економічного ефекту від розвитку дестинацій та їх якісну структуру в межах регіональних економік; урівноважити максимальний попит та пропозицію проєктів розвитку туристично-рекреаційної сфери; розрахувати надлишок та дефіцит туристично-рекреаційних послуг; максимізувати рівень витрат, необхідних для оптимального економічного ефекту щодо розвитку туристично-рекреаційної сфери; оптимізувати розподіл коштів по дестинаціям залежно від потенційних можливостей розвитку туристично-рекреаційної сфери в кожній з них; оптимізувати сезонний розподіл чинників діяльності туристично-рекреаційної сфери; визначити приховану чи наявну межу вартості, пов'язану із зміною основних припущень, вхідних даних та оптимальних результатів розвитку дестинацій. Практика діджиталізації державного управління розвитком туристично-рекреаційної сфери Болгарії (Золоті Піски, Сонячний Берег, Албена та ін.) доводить, що впровадження принципу комплексної і централізованої діджиталізації державного управління їх розвитком заслуговує на позитивну оцінку. Діджиталізація державного управління розвитком туристично-рекреаційної сфери у районі Тихого океану дозволяє визначити місця призначення відвідувачів, які приваблюють в різні сезони, що окреслює особливості дестинацій; логістичні зв'язки та характеристики транспортних та інформаційних засобів для реалізації можливостей зв’язку між пунктом відправлення і пунктом призначення у певному періоді часу. У країнах Південної Адріатики діджиталізація державного управління розвитком туристично-рекреаційної сфери дозволяє обґрунтувати розрахункові та проєктні кошториси відновлення дестинацій. Діджиталізація державного управління розвитком дестинацій Франції дає підставу для прийняття державних рішень з виконання проєктних розробок програм опанування сприятливими для туризму і рекреації територіями та регламентувати основні параметри їхнього розвитку. У США діджиталізація Національної служби парків дозволяє реалізувати проєкти щодо створення заповідників і туристично-рекреаційних центрів в історичних містах. В статье обобщен мировой опыт диджитализации государственного управления развитием туристско-рекреационной сферы и демонстрируется целесообразность внедрения диджитализации в адаптации государственного управления к реалиям современного мира. Показано, что в мировой практике диджитализация государственного управления развитием туристско-рекреационной сферы основывается на статистическом описании туристско-рекреационных проблем; создании моделей прогнозирования последствий государственных решений по развитию туристско-рекреационной сферы; средствах измерения экономической эффективности развития разнообразных форм организации использования свободного времени населения. В частности, диджитализация государственного управления развитием туристско-рекреационной сферы Израиля, Турции и Пуэрто-Рико демонстрирует целесообразность цели диджитализации по государственному решению проблем управления интенсивностью потоков посетителей из центров сосредоточения населения в дестинации и прогнозирования экономического эффекта от этого. В Израиле диджитализация государственного управления развитием туристско-рекреационной сферы преследует цель увеличения объемов иностранной валюты, поступающей в страну благодаря туризму, и ее доли в доходах бюджета, а также максимальную экономию ресурсов на развитие местного туризма. Диджитализация министерства туризма Турции позволяет принимать государственные решения по оценке вероятного и оптимального экономического эффекта от развития дестинаций и их качественной структуры внутри региональной экономики; уравновесить максимальный спрос и предложение проектов развития туристско-рекреационной сферы; рассчитать излишек и дефицит туристско-рекреационных услуг; максимизировать уровень затрат, необходимых для оптимального экономического эффекта по развитию туристско-рекреационной сферы; оптимизировать распределение средств по дестинациям в зависимости от потенциальных возможностей развития туристско-рекреационной сферы в каждой из них; оптимизировать сезонное распределение факторов деятельности туристско-рекреационной сферы; определить скрытый или имеющийся предел стоимости, связанный с изменением основных предположений, входных данных и оптимальных результатов развития дестинаций. Практика диджитализации государственного управления развитием туристско-рекреационной сферы Болгарии (Золотые Пески, Солнечный Берег, Албена и др.) показывает, что внедрение принципа комплексной и централизованной диджитализации государственного управления их развитием заслуживает положительной оценки. Диджитализация государственного управления развитием туристско-рекреационной сферы в районе Тихого океана позволяет определить места назначения посетителей, которые привлекают посетителей в разные сезоны, что определяет особенности дестинаций; логистические связи и характеристики транспортных и информационных средств для реализации возможностей связи между пунктом отправления и пунктом назначения в определенный период времени. В странах Южной Адриатики диджитализация государственного управления развитием туристско-рекреационной сферы позволяет обосновать расчетные и проектные сметы обновления дестинаций. Диджитализация государственного управления развитием дестинаций Франции дает основание для принятия государственных решений по выполнению проектных разработок программ использования благоприятных для туризма и рекреации территорий и регламентировать основные параметры их развития. В США диджитализация Национальной службы парков позволяет реализовать проекты по созданию заповедников и туристско-рекреационных центров в исторических городах.